2018
DOI: 10.1007/s10735-017-9752-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of YAP and TAZ during orthodontic tooth movement in rats

Abstract: Orthodontic tooth movement (OTM) is a periodontal tissue remodeling and regeneration process that is caused by bio-mechanical stimulation. This mechanical-chemical transduction process involves a variety of biological factors and signaling pathways. It has been shown that the Hippo-YAP/TAZ signaling pathway plays a pivotal role in the mechanical-chemical signal transduction process. Moreover, YAP and TAZ proteins interact with RUNX family proteins via different mechanisms. To explore the regulation of the Hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 22 publications
5
23
0
Order By: Relevance
“…In consistence with the abovementioned investigations, the present study revealed that CTS‐induced osteogenic differentiation of PDLCs via the activation of TAZ, as evidenced by the enhanced expression and nucleus localization of TAZ and its binding with Cbfα1. Moreover, our results further extended the in vivo immunohistochemistry findings from rats with OTM, in which TAZ co‐localize with Cbfα1 on both tension and compression side of the periodontal tissues …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In consistence with the abovementioned investigations, the present study revealed that CTS‐induced osteogenic differentiation of PDLCs via the activation of TAZ, as evidenced by the enhanced expression and nucleus localization of TAZ and its binding with Cbfα1. Moreover, our results further extended the in vivo immunohistochemistry findings from rats with OTM, in which TAZ co‐localize with Cbfα1 on both tension and compression side of the periodontal tissues …”
Section: Discussionsupporting
confidence: 81%
“…ent study revealed that CTS-induced osteogenic differentiation of PDLCs via the activation of TAZ, as evidenced by the enhanced expression and nucleus localization of TAZ and its binding with Cbfα1.Moreover, our results further extended the in vivo immunohistochemistry findings from rats with OTM, in which TAZ co-localize with Cbfα1 on both tension and compression side of the periodontal tissues 14. Although it has been well established that the canonical Wnt/β-catenin signaling is of great importance for mechanosensation and mechanotransduction in osteogenic commitment of osteocytes,[28][29][30] there still exists limited evidence with regard to F I G U R E 1 Cyclic tensile stress induces the osteogenic differentiation of PDLCs.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies reported that activation of YAP could induce osteogenic differentiation in MSCs [ 1 , 24 ]. Xu et al proved that YAP/TAZ was involved in the process of periodontal tissue remodeling during OTM in rat [ 25 ]. Furthermore, they demonstrated that knockdown of YAP induced the apoptosis and inhibited the proliferation of human periodontal ligament stem cells (h-PDLSCs) through crosstalk between Erk and Bcl-2 signaling pathway, suggesting that YAP signaling pathway participated in regulating biological behaviors of h-PDLSCs [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…We further stimulated fibroblasts and pre‐osteoblasts with cyclic force to confirm our in vivo results and observed significant activation of Hippo‐YAP pathway upon abnormal stress transmission. In previous studies, YAP and TAZ were shown to be associated with tissue regeneration (Huelter‐Hassler, Tomakidi, Steinberg, & Jung, ; Sun et al., ; Zheng et al., ). In our study, OE aggravated bone loss caused by P.g colonization, while the OE only group did not show severe bone loss and osteoclastic activity, consistent with previous research.…”
Section: Discussionmentioning
confidence: 92%